Advances in the management of fibromyalgia: what is the state of the art?. (24th May 2022) - Staud, Roland
ABSTRACT: Introduction: Fibromyalgia (FM) is a chronic pain syndrome associated with fatigue, insomnia, dyscognition, and emotional distress. Critical illness mechanisms include central sensitization to nociceptive and non-nociceptive stimuli often resulting in hypersensitivity to all sensory input. Areas Covered: The clinical presentation of FM can vary widely and therefore requires therapies tailored to each patient's set of symptoms. This manuscript examines currently prescribed therapeutic approaches supported by empirical evidence as well as promising novel treatments. Although pharmacological therapy until now has been only moderately effective for FM symptoms, it represents a critical component of every treatment plan. Expert opinion: Currently approved pharmacological therapies for FM symptoms have limited but proven effectiveness. Novel therapies with cannabinoids and naltrexone appear promising. Recent functional imaging studies of FM have discovered multiple brain network abnormalities that may provide novel targets for mechanism-based therapies. Future treatment approaches, however, need to improve more than clinical pain but also other FM domains like fatigue, insomnia, and distress.